Examining the role of accounting information systems on a firm’s performance: A technology acceptance model approach - Alhumoudi, Hamad; Johri, Amar (Edelweiss Applied Science and Technology, 2024)
This study investigates the impact of Accounting Information Systems (AIS) on firm performance (FP) through the lens of the Technology Acceptance Model (TAM). It employs a quantitative and qualitative methodology to analyze the relationship between AIS and firm performance, utilizing data collected from a sample of 408 accountants across various industries in India. An online survey, through a structured questionnaire, was conducted among the respondents to explore their perception towards the effectiveness of AIS on a firm's performance. By measuring critical constructs within the TAM framework, including perceived usefulness and perceived ease of use, this study aims to ascertain the extent to which AIS adoption influences firm performance metrics such as financial efficiency, decision-making effectiveness, and overall competitiveness. The results obtained from the study indicated that all the factors significantly influence the firm's performance; however, ease of use, efficiency, and reliability of AIS have a highly positive impact on the firm's performance. The findings of this study are expected to contribute to both theoretical understanding and practical implications for accountants to understand the value proposition of AIS technologies and for policymakers to design supportive frameworks and incentives to facilitate the widespread adoption of AIS.